Intersecting Research and Practice: Effort to Both Acknowledge and Act on How the System Impacts Children and Youth in Care / Anti-Oppressive Child and Youth Care: Critical Conversations - Gilmore, Wraychel (Journal of Childhood Studies, 2026)
Anti-Oppressive Child and Youth Care: Critical Conversations (Andrea Christensen, editor, Canadian Scholars, 2025) both educates and advocates for identity recognition and change within the child and youth care sector. Diverse voices not always present in the past decades of professional dialogue for the sector unpack, explore, and share about the necessity for anti-oppressive approaches, why they should exist, and how they can be implemented.